2021
DOI: 10.1136/bjophthalmol-2020-317547
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of progression in untreated keratoconus: a Save Sight Keratoconus Registry study

Abstract: AimsWe set out to identify risk factors for progression in untreated keratoconus patients from 34 centres across Australia, New Zealand, Spain and Italy.MethodsPatients were divided into ‘progressors’ and ‘stable’ patients for each clinical parameter: visual acuity (VA), steepest keratometry (maximum keratometry (Max-K)) and thinnest corneal thickness (TCT). Primary outcomes were the proportion of eyes with sustained progression in VA, Max-K or TCT within 3 years. Secondary outcomes included predictors of prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 37 publications
2
25
1
Order By: Relevance
“…The study had several strengths. Our large cohort of routine clinical practice data from multiple international sites likely reflects the QoL impact of eye diseases in the real world 29–32 . This study has confirmed that the use of IVI in SSR modules is appropriate, and misguided or false conclusions are not derived from the future IVI use in the registry.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…The study had several strengths. Our large cohort of routine clinical practice data from multiple international sites likely reflects the QoL impact of eye diseases in the real world 29–32 . This study has confirmed that the use of IVI in SSR modules is appropriate, and misguided or false conclusions are not derived from the future IVI use in the registry.…”
Section: Discussionsupporting
confidence: 61%
“…This descriptive, cross‐sectional study was conducted using the prospectively designed SSR database (http://savesightregistries.org/). The SSR is a multi‐national web‐based database of patients with eye diseases that allows routine collection of clinical and patient‐reported data and monitoring of outcomes over time 29–32 . The current study included the participants from 44 practices with an established diagnosis of keratoconus, AMD, RVO or DME in one or both eyes who self‐administered the IVI questionnaire.…”
Section: Methodsmentioning
confidence: 99%
“…Keratoconus tends to progress more rapidly in younger subjects and has been shown to plateau with age [ 6 , 14 , 15 , 33 , 34 ]. The Collaborative Longitudinal Evaluation of Keratoconus (CLEK) Study evaluating the natural history of keratoconus reported that a presenting age younger than 35 years is a significant predictor of a 3D or more increase in K1 [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Corneal topography, tomography, and pachymetry are the principal parameters used in the diagnosis and follow-up of progressive KC [ 5 ]. Numerous studies have identified baseline corneal characteristics that are associated with more severe disease and progression in these parameters [ 6 , 14 , 15 , 33 , 38 ]. In a study evaluating prognostic factors of KC progression that led to corneal transplantation, Tuft et al found that eyes with steeper baseline K1 and K2 required a shorter time to penetrate keratoplasty [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation